Realizing Excellent n‐ and p‐Type Niobium‐Based Half‐Heusler Compounds Based on Thermoelectric Properties and High‐Temperature Stability - Wanthana Silpawilawan; Sora‐at Tanuslip; Raju Chetty; Michihiro Ohta; Yuji Ohishi; Hiroaki Muta; Ken Kurosaki (Advanced Electronic Materials, 2020)
Abstract Half‐Heusler (HH) compounds are currently promising thermoelectric (TE) materials due to their outstanding performance. For reliable n‐ and p‐type HH compounds, the dimensionless figure of merit zT is reported as greater than unity. However, to develop a high‐performance TE module, zT, high‐temperature stability, and compatibility of n‐ and p‐type materials are key parameters. Here, the TE and thermomechanical properties and the high‐temperature stability of Nb‐based HH compounds: n‐type Nb0.75M0.1CoSb and p‐type FeNb0.9M0.1Sb (M = Ti, Zr, Hf) are investigated. The results reveal that the Ti‐doped system exhibits better TE and thermomechanical properties than the Zr‐ and Hf‐doped systems. Furthermore, the Ti‐doped samples show good high‐temperature stability in an inert atmosphere up to 773 K and in air up to 673 K. The performance of a 2π‐module based on the best n‐type Nb0.75Ti0.1CoSb and p‐type FeNb0.9Ti0.1Sb is simulated by using the 3D finite element method. The maximum output power density (ωmax) and conversion efficiency (ηmax) of 2.3 W cm−2 and 4.0%, respectively, are obtained when the cold‐ and hot‐side temperatures are 298 and 773 K, respectively.